2018
DOI: 10.1186/s12906-018-2307-5
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine use among children with mental health issues: results from the National Health Interview Survey

Abstract: BackgroundMental health issues in children have become a serious public health concern in the U.S. within the past few decades. Emerging evidence suggests that Complementary and Alternative Medicine (CAM) can be beneficial for various mental health issues. However, little is known about the prevalence, reasons, and associated factors of CAM use among this population in the U.S. The purpose of this study is to examine the characteristics of CAM use among U.S. children with mental health issues.MethodsUtilizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 71 publications
1
21
0
2
Order By: Relevance
“…33 For instance, using NAMCS data, investigators have found that routine or preventive visits are the most frequent reason that children see office-based physicians. 34 However, CHA use is higher among children with cancer, 35 mental health issues, 36 and musculoskeletal conditions. 37 The current findings add to the literature by showing physician-based national estimates regarding sex differences in recommendations of CHA.…”
Section: Discussionmentioning
confidence: 99%
“…33 For instance, using NAMCS data, investigators have found that routine or preventive visits are the most frequent reason that children see office-based physicians. 34 However, CHA use is higher among children with cancer, 35 mental health issues, 36 and musculoskeletal conditions. 37 The current findings add to the literature by showing physician-based national estimates regarding sex differences in recommendations of CHA.…”
Section: Discussionmentioning
confidence: 99%
“…Some non-prescription drugs—such as some antihistamines and melatonin—are among the most used substances for managing insomnia in children [ 12 ]. Complementary and Alternative Medicine (CAM) is also widely used for children with ASD [ 13 , 14 ], or other mental issues, given that the majority of parents perceive these therapies as a helpful and holistic therapeutic approach [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“… 5 7 16 29 In a recent study, Wang et al identified that American children with mental health disorders are more commonly using complementary treatments compared with those without (19.2% compared with 10.1%, p<0.001) and herbal medicines are the most frequently used modality. 30 …”
Section: Discussionmentioning
confidence: 99%